2003
DOI: 10.1289/ehp.6042
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to high levels of particulate air pollution and small airway remodeling.

Abstract: Recent evidence suggests that chronic exposure to high levels of ambient particulate matter (PM) is associated with decreased pulmonary function and the development of chronic airflow obstruction. To investigate the possible role of PM-induced abnormalities in the small airways in these functional changes, we examined histologic sections from the lungs of 20 women from Mexico City, a high PM locale. All subjects were lifelong residents of Mexico City, were never-smokers, never had occupational dust exposure, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(128 citation statements)
references
References 29 publications
10
111
0
6
Order By: Relevance
“…These new findings should not be misinterpreted to indicate that high levels of air pollution have little or no effect on the lungs of never smokers. In never smokers, there is clear evidence that high levels of air pollution cause structural damage in the lung periphery 6,7,16 and accelerate decline in lung function. 17 Nonsmokers exposed to high levels of air pollution will probably not die of COPD, but they may develop a higher-than-normal risk of death from pneumonia or influenza consistent with the present data.…”
Section: Discussionmentioning
confidence: 99%
“…These new findings should not be misinterpreted to indicate that high levels of air pollution have little or no effect on the lungs of never smokers. In never smokers, there is clear evidence that high levels of air pollution cause structural damage in the lung periphery 6,7,16 and accelerate decline in lung function. 17 Nonsmokers exposed to high levels of air pollution will probably not die of COPD, but they may develop a higher-than-normal risk of death from pneumonia or influenza consistent with the present data.…”
Section: Discussionmentioning
confidence: 99%
“…347 There is evidence, even in nonsmokers, that long-term exposure to PM air pollution results in pulmonary retention of fine particles and small airway remodeling and contributes to COPD. 348,349 Epidemiologic evidence that supports this hypothesis includes various studies that have observed that longterm PM exposures are associated with deficits in lung function 350 -354 and increased symptoms of obstructive airway disease, such as chronic cough, bronchitis, and chest illness. 25,[355][356][357][358][359] Recently published results from the Southern California Children's Health Study indicate that exposure to PM 2.5 and other combustion-related air pollutants were significantly associated with deficits in the rate of lung function growth in children (see Figure 2d).…”
Section: Accelerated Progression and Exacerbation Ofmentioning
confidence: 99%
“…Néanmoins, on ne peut exclure que les particules les plus fines aient un effet direct sur les tissus voisins par transcytose, au travers des épithéliums [17]. Une exacerbation et/ou un dérèglement des fonctions épithéliales associés à une exposition répétée aux polluants environnementaux, ozone et PM, peuvent être à l'origine d'une inflammation chronique et d'un remodelage bronchique caractérisé par l'épaississement du tissu musculaire lisse, une métaplasie muqueuse et une fibrose péribronchique [18]. Ces modifications s'observent aussi chez des patients atteints de BPCO et d'asthme.…”
Section: L'agression Oxydante Conduit-elle Au Remodelage Bronchique ?unclassified
“…La cascade proapoptotique est alors déclenchée par la chute du potentiel transmembranaire de la mitochondrie et la libération cytosolique du cytochrome c. Les macrophages, sans doute parce qu'ils ont une plus grande capacité de phagocytose, sont plus sensibles que les cellules épithéliales à l'induction de l'apoptose [19]. Cette constatation est importante pour expliquer la persistance des particules dans le poumon profond (zones alvéolaires) associée à l'inflammation chronique et au remodelage bronchique [18]. La découverte récente que les PDi à faible concentration pouvaient, par contre, inhiber l'apoptose dans la lignée alvéolaire humaine A549 en provoquant la baisse d'expression de la protéine p21, particulièrement importante dans le contrôle du cycle cellulaire, pose la question de leur rôle à long terme sur la prolifération cellulaire et l'hyperplasie [20].…”
Section: L'agression Oxydante Conduit-elle Au Remodelage Bronchique ?unclassified